Smartphone-Based Digital KWH Meter and SMS Gateway in Residential Homes - Moh. Muzakki Firmansyah; Akhmad Ahfas; Syamsudduha Syahrorini; Dwi Hadidjaja Rasjid Saputra (Universitas Muhammadiyah Sidoarjo, 2021)
Consumers need to be conscious of electrical energy usage every day, in accordance with the need for power consumption. Then a kWHmeter is needed that will provide this data so that people can handle it. This study developed a kWHmeter that can show Smartphone voltage, current, fuel, overall usage and projected electricity costs and can submit alerts when electricity use is near to a preset limit using the SDM230 Modbus, Arduino Uno, NodeMCU ESP8266, GSM module, MySQL database. In this research, with a precision of 98.704% for voltage, 39.88% for current, 53.333% for energy usage, and 26.14% for power energy, test results of the instrument can be operated very effectively. The method will also submit SMS alerts with an average speed of 0.6 seconds for this analysis and the android program is made to show data on the 100% accuracy of energy usage and 99.508% accuracy of cost estimates.